Reestruturação do gênero Deois Fennah; descrição de um novo gênero e de novas espécies (Homoptera, Cercopidae, Tomaspidinae) - Costa,Antonio Claudio Ferreira da (2002)
Restructure of the genus Deois Fennah; description of a new genus and new species (Homoptera, Cercopidae, Tomaspidinae). The genus Deois Fennah is reviewed and some changes in the taxonomy are introduced. The genus and its four subgenera are redefined, having now the following composition: 1) subgenus Deois (Deois) with: D. (D.) correntina (Berg, 1879), D. (D.) grandis Sakakibara, 1979, D. (D.) knoblauchii (Berg, 1879) (formerly in D. (Pandysia)), D. (D.) morialis (China & Myers, 1934), D. (D.) mourei Cavichioli & Sakakibara, 1994, D. (D.) piraporae Sakakibara, 1979, D. (D.) pseudoflavopicta (Lallemand, 1938) comb. nov. (formerly in Mahanarva) = D. (D.) similis Sakakibara, 1979 syn. nov., D. (D.) rubropicta Sakakibara, 1979, D. (D.) spinulata sp. nov., D. (D.) terrea (Germar, 1821), D. (D.) uniformis (Distant, 1909). 2) subgenus Deois (Pandysia) with: D. (P.) bergi sp. nov., D. (P.) crenulata sp. nov., D. (P.) schach (Fabricius, 1787) = Sphenorhyna transiens Walker, 1851 syn. nov.. 3) Deois (Fennahia) with: D. (F.) coerulea (Lallemand, 1924), D. (F.) flexuosa (Walker, 1851). 4) Deois (Acanthodeois) with: D. (A.) flavopicta (Stål, 1854), Deois (A.) incompleta (Walker, 1851). The genus Orodamnis Fennah, 1953 stat. nov. (formerly Deois (Orodamnis)) with: Orodamnis rhynchosporae (China & Myers, 1934) comb. nov. The genus Deoisella gen. nov. is described for: Deoisella fasciata sp. nov. (type species) and Deoisella picklesi (China & Myers, 1934) comb. nov.